A and b are the 2 smaller sides, and c = hypotenus; only for right triangles,
Pythagorean Theorem states that:
![{c}^{2} = {a}^{2} + {b}^{2}](https://tex.z-dn.net/?f=%20%7Bc%7D%5E%7B2%7D%20%20%3D%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20)
given c = 6 in., a = 2 in.
![{c}^{2} = {a}^{2} + {b}^{2} \\ {6}^{2} = {2}^{2} + {b}^{2} \\ {b}^{2} = {6}^{2} - {2}^{2} = 36 - 4 \\ \sqrt{ {b}^{2} } = \sqrt{36 - 4} = \sqrt{32}](https://tex.z-dn.net/?f=%20%7Bc%7D%5E%7B2%7D%20%20%3D%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%5C%5C%20%20%7B6%7D%5E%7B2%7D%20%20%3D%20%20%7B2%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%5C%5C%20%7Bb%7D%5E%7B2%7D%20%3D%20%20%7B6%7D%5E%7B2%7D%20%20-%20%20%7B2%7D%5E%7B2%7D%20%3D%2036%20-%204%20%20%20%5C%5C%20%5Csqrt%7B%20%7Bb%7D%5E%7B2%7D%20%7D%20%20%3D%20%20%5Csqrt%7B36%20-%204%7D%20%20%3D%20%20%5Csqrt%7B32%7D%20%20)
![b = \sqrt{32} = \sqrt{16} \times \sqrt{2} = 4 \sqrt{2} \\ b = 5.66 \: inches](https://tex.z-dn.net/?f=b%20%3D%20%20%5Csqrt%7B32%7D%20%20%20%3D%20%20%5Csqrt%7B16%7D%20%20%5Ctimes%20%20%5Csqrt%7B2%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5C%5C%20b%20%3D%205.66%20%5C%3A%20inches)
So the three side are 2, 6, and 5.66 inches
Answer:
![Total = 1.02n](https://tex.z-dn.net/?f=Total%20%3D%201.02n)
Step-by-step explanation:
Given
![Earnings = n](https://tex.z-dn.net/?f=Earnings%20%3D%20n)
--- <em>not 296</em>
![Total = n + 0.02n](https://tex.z-dn.net/?f=Total%20%3D%20n%20%2B%200.02n)
Required
Simplify the expression for total earning
The total amount is derived from:
![Total = Earnings + Raise * Earnings](https://tex.z-dn.net/?f=Total%20%3D%20Earnings%20%2B%20Raise%20%2A%20Earnings)
![Total = n + 2\% * n](https://tex.z-dn.net/?f=Total%20%3D%20n%20%2B%202%5C%25%20%2A%20n)
Express percentage as decimal
![Total = n + 0.02 * n](https://tex.z-dn.net/?f=Total%20%3D%20n%20%2B%200.02%20%2A%20n)
Now, we can solve further:
![Total = n + 0.02n](https://tex.z-dn.net/?f=Total%20%3D%20n%20%2B%200.02n)
![Total = 1.02n](https://tex.z-dn.net/?f=Total%20%3D%201.02n)
<em>Hence, the simplified expression is 1.02n</em>
Answer:
x = - 1
Step-by-step explanation:
Given
3x + 2 = y and y = - 1
Substitute y = - 1 into the equation and solve for x, that is
3x + 2 = - 1 ( subtract 2 from both sides )
3x = - 3 ( divide both sides by 3 )
x = - 1
This is verified by the point on the graph with coordinates (- 1, - 1)
Since (f/g)(x) = f(x)/g(x) for x to be in the domain of (f/g)(x) it must be in the domain of f and in the domain of g. You also need to insure that g(x) is not zero since f(x) is divided by g(x). Thus there are 3 conditions. x must be in the domain of f: f(x) = 3x -5 and all real numbers x are in the domain of x.
Given f(x) = 2x + 3 and g(x) = –x2 + 5, find ( f o f )(x).
( f o f )(x) = f ( f (x))
= f (2x + 3)
= 2( ) + 3 ... setting up to insert the input
= 2(2x + 3) + 3
= 4x + 6 + 3
= 4x + 9
Given f(x) = 2x + 3 and g(x) = –x2 + 5, find (g o g)(x).
(g o g)(x) = g(g(x))
= –( )2 + 5 ... setting up to insert the input
= –(–x2 + 5)2 + 5
= –(x4 – 10x2 + 25) + 5
= –x4 + 10x2 – 25 + 5
= –x4 + 10x2 – 20
D. y, because Triangle JHK is similar to triangle LMK